Customer Relationship Management Communication Strategy to Increase Customers via Livin’ by Mandiri - Wulandari, Siti Hardiati; Ambulani, Nur; Astuti, Marhanani Tri (Universitas Prof. Dr. Moestopo (Beragama), 2025)
Banking competition with digital transformation has encouraged innovation in similar applications launched by banks, such as Livin' by Mandiri, BCA Mobile, BRImo, and others, which also offer superior features. This research aims to analyze the digital communication strategy implemented by PT. Bank Mandiri (Persero) Tbk through Livin' by Mandiri application increases the number of customers in Region IV Jakarta Kebon Sirih Area. This research uses a qualitative descriptive approach with data collection techniques through in-depth interviews, observation, documentation and analysis using Customer Relationship Management (CRM) theory. This research concludes that 1) Livin' by Mandiri's communication strategy is carried out with digital literacy through community-based educational campaigns, video tutorials and outreach programs. 2) Challenges in Livin' by Mandiri digital communication campaign include limitations on incompatible devices, transaction failures due to slow or disconnected connections, educational background, age and demographic barriers in understanding digital features, as well as concerns about data security and habits that are difficult to change. 3) Bank Mandiri's successful actions to overcome challenges in increasing Livin' by Mandiri application customers include promotions and education to the public and institutions, which have had a positive impact on increasing application users by up to 76% and increasing customer loyalty.